Rural Energy Source and Its Contribution to Climate Change: The Case of Negele Arsi District, Oromia Region, Ethiopia - Gemedo Mohammed Bona; Zerihun Demrew Yigezu (The Scientific World Journal)
The use of traditional biomass in developing countries such as Ethiopia accounts for approximately 90% of the total primary energy consumption at the household level. Such heavy dependency threatens the natural forest ecosystem and contributes to climate change. However, empirical evidence on the extent of fuelwood consumption is limited. This study was therefore carried out to investigate the status of firewood consumption in the Negele Arsi District of Oromia Region, Ethiopia, and its contribution to climate change. Door-to-door surveys and measurements were made to estimate the extent of firewood consumption and the resultant greenhouse gas (CO2e) emissions at the household level. The major type of woody species used as household energy sources and the amount of firewood saved while using the improved stove were also predicted through kitchen performance tests. The findings showed that 84.5% of the energy needed for home-based activities was fulfilled by firewood. Eucalyptus species, Podocarpus facaltus and Acacia etbaica, were the most common tree species used as household energy sources in the district. It was found that 17.02 tons of firewood was consumed, and 18 × 103 tCO2e was emitted annually at the household level. Baking Injera using Mirt stove was found to reduce firewood consumption by approximately 25% compared to a traditional open stone stove. The study showed that firewood consumption is the main cause of deforestation in the district and has a large contribution to climate change. Hence, coordinated effort and appropriate interventions are needed to avert the situation.